2022
DOI: 10.3390/microorganisms10081649
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cutibacterium acnes in Sarcoidosis: From Antigen to Treatable Trait?

Abstract: Cutibacterium acnes (C. acnes, formerly Propionibacterium acnes) is considered to be a non-pathogenic resident of the human skin, as well as mucosal surfaces. However, it also has been demonstrated that C. acnes plays a pathogenic role in diseases such as acne vulgaris or implant infections after orthopedic surgery. Besides a role in infectious disease, this bacterium also seems to harbor immunomodulatory effects demonstrated by studies using C. acnes to enhance anti-tumor activity in various cancers or vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 111 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Cutibacterium acnes is a skin commensal, ubiquitously distributed among healthy individuals [5] . Cutibacterium acnes produces lipases which cause inflammation of the skin and other parts of the body [14] , [50] , [51] , [52] . Cutibacterium acnes has also been detected in granuloma tissue via immunohistochemistry and is believed to be involved in the pathogenesis of sarcoidosis [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Cutibacterium acnes is a skin commensal, ubiquitously distributed among healthy individuals [5] . Cutibacterium acnes produces lipases which cause inflammation of the skin and other parts of the body [14] , [50] , [51] , [52] . Cutibacterium acnes has also been detected in granuloma tissue via immunohistochemistry and is believed to be involved in the pathogenesis of sarcoidosis [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study conducted by Drake et al demonstrated that antituberculotic treatment in sarcoidosis patients with detected tubercle bacilli components in pathological samples of nodules did not effectively improve their lung function [ 50 ]. Despite several researchers successfully isolated Propionibacterium acnes from samples of patients with sarcoidosis and constructed sarcoidosis mouse models using in vitro cultured Cutibacterium acnes and M. tuberculosis and their derivatives, however, the modalities of modeling and the conditions of nodule formation still differed significantly from the occurrence scenes of sarcoidosis in clinical patients [ [51] , [52] , [53] , [54] , [55] ]. Therefore, further investigation was still needed to confirm the direct contribution of microbial infections and their related mechanisms in the development of sarcoidosis.…”
Section: Sarcoidosis Triggered By Foreign Antigensmentioning
confidence: 99%
“…Granuloma formation occurs only in individuals predisposed to a hypersensitive Th1 immune response against the intracellular proliferation of C. acnes . An allergic reaction to intracellular C. acnes proliferation seems to be caused by a different mechanism than the immunomodulatory effect of C. acnes itself [ 74 ]. Successful confinement of C. acnes that is proliferating intracellularly via granuloma formation prevents further spread of infective C. acnes to other cells, which resolves the granulomatous inflammation that leads to spontaneous remission in many sarcoidosis patients.…”
Section: Pathogenesis Of Sarcoidosis Caused By C Acnesmentioning
confidence: 99%
“…Combination therapy with steroids and antimicrobials is currently under clinical trial investigation in Japanese patients with cardiac sarcoidosis [ 91 ]; the efficacy of the combination therapy is being compared between a control group receiving only steroids according to the current guideline [ 92 ] and an antimicrobial group receiving doxycycline and clarithromycin in addition to the steroids. A clinical trial of anti- C. acnes antimicrobial therapy using doxycycline and azithromycin in Dutch patients with sarcoidosis is also currently underway to compare the efficacy of the antimicrobial therapy between patients with or without detection of C. acnes with the PAB antibody in their biopsy samples [ 74 ]. In the study, the automated immunohistochemical method used to detect C. acnes with the PAB antibody should be standardized, however, because the sensitivity differs remarkably between the Leica and Ventana systems [ 36 ].…”
Section: Treatment Strategies For Refractory Sarcoidosismentioning
confidence: 99%